please help asap!!!!

Answer:
Step-by-step explanation:
Given functions are,
f(x) = [tex]\sqrt{x} +3[/tex]
g(x) = 4 - [tex]\sqrt{x}[/tex]
22). (f - g)(x) = f(x) - g(x)
= [tex]\sqrt{x}+3-(4 - \sqrt{x} )[/tex]
= [tex]\sqrt{x} +3-4+\sqrt{x}[/tex]
= [tex]2\sqrt{x}-1[/tex]
Domain of the function will be [0, ∞).
23). (f . g)(x) = f(x) × g(x)
= [tex](\sqrt{x}+3)(4-\sqrt{x} )[/tex]
= [tex]4(\sqrt{x}+3)-\sqrt{x}(\sqrt{x}+3)[/tex]
= [tex]4\sqrt{x} +12-x-3\sqrt{x}[/tex]
= [tex]-x+\sqrt{x}+12[/tex]
Domain of the function will be [0, ∞).